Finnish teachers’ and students’ programming motivation and their role in teaching and learning computational thinking - Fagerlund, Janne; Leino, Kaisa; Kiuru, Noona; Niilo-Rämä, Mikko (Frontiers in Education, 2022)
Despite the growing importance of teaching and learning computational thinking (CT) through programming in schools, research has shown major individual differences in teachers’ instruction emphasis and students’ skills in these topics. This study aims to shed further light on the role that teachers’ and students’ programming motivation plays in CT. The topic is approached from the viewpoint of the self-determination theory, which can help to understand teachers’ instruction and students’ learning. Our sample consisted of Finnish Grade 8 teachers (N = 1,853) and students (N = 2,546) who participated in the International Computer and Information Literacy Study (ICILS) in 2018. Focusing on teachers’ CT instruction emphasis, students’ CT test scores, and the Intrinsic Motivation Inventory, we investigate (1) distributions of teachers’ and students’ responses to intrinsic and extrinsic programming motivation questions, (2) associations between teachers’ and students’ programming motivation and their background factors, and (3) associations between programming motivation and teachers’ CT instruction emphasis and students’ CT test scores. The data was analyzed by examining descriptive statistics, computing mean differences and correlation coefficients and by performing (multiple) linear regression models. The results showed that teachers had high extrinsic programming motivation, but the extent of their intrinsic programming motivation varied widely based on their prior programming teaching experience, subject taught, and gender. Students, in turn, reported both high intrinsic and extrinsic motivation toward programming, but boys were generally more motivated for programming than girls. High programming motivation was moderately related to teachers’ higher CT instruction emphasis and students’ higher CT test scores. The findings give a strong incentive to pay attention to increasing especially girls’ programming motivation and providing teachers with positive CT experiences relevant to their subject and with a particular objective to increase intrinsic motivation especially among teachers who lack prior programming teaching experience and interest in the topic.